INTEGRASI STRUKTUR DAN UNIT: TEORI POLITIK LUAR NEGERI DALAM PERSPEKTIF REALISME NEOKLASIK - Rosyidin, Mohamad (UI Scholars Hub, 2010)
When studying foreign policy, most students of international relations employ decision making theory to explain the origin of states policy. They often believe that it can account for appropriately and make simple analysis regarding why certain strategies taken by state. As a result, the decision making theory has been dominated foreign policy research, even associated with foreign policy itself. As an analytical tool, decision making theory stressed solely on domestic factors (unit level explanation) and seems likely overlooked systemic factors as independent variable. This article will introduces neoclassical realism as an alternative theory of foreign policy. This article will shows that neoclassical realism fills the gap between structural approach and unit level approach. In doing so, adherents of neoclassical realism school of thought incorporated structural constraint as single independent variable and domestic factors as intervening variable. The aim of this article is to abandon from 'domestification' in decision making theory focus of analysis by introducing contemporary realist theory of state action.